2018
DOI: 10.3390/buildings8070091
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Comparative Evaluation of Building and District Control-Oriented Energy Retrofit Scenarios

Abstract: This paper presents work undertaken as part of the European H2020 project OptEEmAL (Optimized Energy Efficient Design Platform for Refurbishment at District Level), toward development of a decision-support platform for building and district refurbishment interventions. We describe a methodology for generation and evaluation of refurbishment scenarios for building and districts with particular emphasis on "active" energy conservation measures (i.e., installation or replacement of heating, ventilation, air condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…The proposed system assumes the purchase of fans by the museum and the configuration of the correct control algorithm basing on instantaneous T and RH measurements. We did not consider specific HVAC devices or their efficiency, which may be the subject of future research, especially since some recent studies [54] showed considerable variations in energy consumption depending on the HVAC efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed system assumes the purchase of fans by the museum and the configuration of the correct control algorithm basing on instantaneous T and RH measurements. We did not consider specific HVAC devices or their efficiency, which may be the subject of future research, especially since some recent studies [54] showed considerable variations in energy consumption depending on the HVAC efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The Wi-Fi-based occupancy schedule decreased energy consumption of the HVAC system by at least 50%. Much broader research has been conducted under the OptEEmAl project funded by the EU Horizon 2020 program to improve the energy efficiency of entire residential districts [46]. As part of the project, new districts will be designed, and the existing districts will be retrofitted by combining passive (upgrading the building envelope through the installation of internal and external insulation) and active measures (installation of new HVACs, replacement of outdated units), using renewables and implementing control strategies to guarantee their energy efficiency.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…The calculation of these DPIs is done through a set of simulation tools that have been integrated into OptEEmAL in order to calculate the indicators and then to post-process and aggregate them to compute the DPIs. In total, there are four tools that enable these calculations: Energy Plus [19] (to compute the energy demand related indicators); a tool specifically developed for OptEEmAL called the HVAC tool [20] (to compute the energy consumption related indicators); the NEST tool [21] (to compute the environmental indicators); and the Economic and Social Indicators' Calculation Tool [22], developed to compute the indicators in these two fields. All these tools together form the Simulation toolbox of OptEEmAL, which uses as input data the information stored within the DDM and provide as outcome the DPIs computed and post-processed.…”
Section: The Opteemal Toolmentioning
confidence: 99%